Hypnosis for Acute Procedural Pain: A Critical Review. Issue 1 (2nd January 2016) - Kendrick, Cassie; Sliwinski, Jim; Yu, Yimin; Johnson, Aimee; Fisher, William; Kekecs, Zoltán; Elkins, Gary
Abstract: Clinical evidence for the effectiveness of hypnosis in the treatment of acute procedural pain was critically evaluated based on reports from randomized controlled clinical trials (RCTs). Results from the 29 RCTs meeting inclusion criteria suggest that hypnosis decreases pain compared to standard care and attention control groups and that it is at least as effective as comparable adjunct psychological or behavioral therapies. In addition, applying hypnosis in multiple sessions prior to the day of the procedure produced the highest percentage of significant results. Hypnosis was most effective in minor surgical procedures. However, interpretations are limited by considerable risk of bias. Further studies using minimally effective control conditions and systematic control of intervention dose and timing are required to strengthen conclusions.